Interpreting and managing soybean iron chlorosis in Western Kansas - Liesch, Amanda Mae (Kansas State University, 2011)
Soybeans have expanded into Western Kansas during the last 50 years, increasing in area by 14,500%. There are several limitations that come with trying to grow soybeans in this region, including fertility constraints, moisture stress, and improper use of fertilizers. However, the largest constraint at this time seems to be the presence of micronutrient deficiencies, specifically iron. This thesis has an introduction, and three major chapters.The objective of the first study on agronomics was the evaluation of the effect of Fe fertilizer application using foliar and seed-applied methods in combination with variety selection for Fe deficiency management of soybean grown under irrigated conditions in Western Kansas. The second study uses multivariate analysis as an exploratory tool useful in determining simultaneous observation and analysis of more than one variable in a multidimensional space. Factor analysis is used to find underlying factors that one variable alone cannot measure. The objective of this study was to determine the underlying factors and the multi-linear models that are associated with soil parameters that can create Fe chlorosis in the Great Plains. The third study looked at different application rates of seed-applied Fe fertilizer to try and determine the optimum application rate for application of chelated Fe in Western Kansas.
Keywords: Soil Science; Iron Deficiency; Iron Chlorosis; Foliar Fe; Seed Applied Fe; Factor Analysis; Agronomy (0285); Soil Sciences (0481); Sustainability (0640)